News Construction of the Jakarta Gubernatorial Election Contest: A Robert N. Entman Framing Analysis on detikX - Lestari, Anggita; Aditya Fauzi Nurochmat; Hanafi, Hanafi (Yayasan Sinergi Kawula Muda, 2026)
This study examines how detikX framed news coverage of Ridwan Kamil’s candidacy in the 2024 Jakarta Gubernatorial Election, focusing on the article “The Cancellation of RIDO’s Victory Party at the Sultan Hotel,” published on December 2, 2024. Using Robert N. Entman’s framing analysis, the research applies a qualitative approach with data collected through observation, document analysis, and purposive interviews. The findings show that, in defining the problem, detikX highlights the pressure faced by Ridwan Kamil after the quick count results while still portraying his optimism about a potential victory. In diagnosing causes, the report links the situation to Anies Baswedan’s support for Pramono Anung, strategic and communication missteps by Ridwan Kamil, and controversies that damaged his public image, including remarks on single mothers. Through moral judgment, detikX emphasizes the lack of preparedness within the RIDO and KIM Plus teams in anticipating defeat, internal communication weaknesses, and efforts to build a narrative of victimhood or suggest electoral irregularities. The treatment recommendation underscores the urgency of strengthening communication strategies if the election proceeds to a second round. The study’s novelty lies in its micro-level analysis of an investigative digital news platform using Entman’s model. By integrating textual analysis with interviews involving a journalist, a media observer, and a political practitioner, this research provides a nuanced understanding of how online media construct Ridwan Kamil’s political image.